The impact of household health shocks on female time allocation and agricultural labor participation in rural Pakistan - Gajate-Garrido, Gissele (International Food Policy Research Institute, 2015)
There have been few empirical studies in the developing world and the agricultural sector, on the impact of negative health shocks on household well-being. Does the pervasive effect of a negative household-level health shock persist beyond its initial impact and indirectly affect long-run outcomes? What are the channels through which this impact affects household dynamics? To answer these questions this research paper measures the effect of household health shocks on female time allocation and agricultural labor participation in rural Pakistan. To deal with joint determination and measurement error issues, it uses a wide range of covariates found in the 2012 and 2013 Pakistan Rural Household Panel Surveys, including individual, year, and district fixed effects. This paper improves on previous research by providing evidence on the role of changes in female labor supply as an insurance mechanism and shedding light on the nonmonetary consequences of adverse health shocks. Increases in paid workload for women reduce time spent on household chores directly related to child quality. The paper shows how these changes in time allocation affect households’ overall well-being.